Ubiquitin binding by the p62 UBA domain - Adlington, Jennifer (2013)
Over 30 different mutations in p62 UBA have been identified in patients with Paget's disease of bone (PDB). The mechanisms which underlie PDB are poorly understood, although impaired ubiquitin binding has been identified as a mechanism in the onset of disease. However, the decrease in affinity is subtle for many PDB mutants. The p62 UBA is unique amongst UBAs since it exists as a highly stable dimer but binds to ubiquitin as a monomer. The dimerization interface partially occludes the ubiquitin binding interface resulting in competing equilibria. The factors which regulate the affinity of p62 UBA were examined in this thesis.